Property and production in Rosas times: Quilmes 1837 (Quinto Sol, 2013)
Through the analysis of primary sources, a census of individuals affected by direct tax, and the data provided by 1838 electoral rolls, we will attempt to investigate the activities and properties of the population of Quilmes, a district nearby Buenos Aires; in times in which transformations within rural society affected all levels of daily life. Firstly, property sizes are analyzed, differetiating zones within the same district, and making comparisons with other districts of the same hinterland. We also relate these data with the amount of inhabitants in each property. Besides,  we analyze the amount of cattle we find in the district and its degree of concentration, as well as the relationship existing between cattle and land. Finally, and based upon the data so obtained, we speculate about the activities of inhabitants of the biggest district near the city, and its differentiation according to the zone they dwell in.
Keywords: Buenos Aires; hinterland; Quilmes; land; production; nearness